VALUASI SUMBERDAYA AIR (STUDI KASUS KAWASAN MATA AIR TATANEYAN DI KELURAHAN KINILOW I, KECAMATAN TOMOHON UTARA, KOTA TOMOHON) - Rolla A.C. Lopis; O. Esry. H. Laoh; Mex L. Sondakh (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine how how big the valuations of water in the spring Tataneyan located in the Village Kinilow I, District of North Tomohon, Tomohon, by using the concept of economic valuation to calculate the value of the utilization of water resources directly or indirectly. This study was conducted from October to December 2016, using primary and secondary data with sampling technique simple random sampling method and the respondents as many as 30 people. Analysis of the data used is quantitative analysis to identify the value of the value of benefits in the area of water resources in the waters Tataneyan value direct use for domestic households and public bath are also value the presence of fish breeding and agricultural irrigation water spinach. The results showed that the area of the springs Tataneyan have a total economic benefit value of Rp. 1.586.715.372/year. By calculating the average value of the obtained surplus WTP consumers showed the overall consumer receives more benefits than the actual price that is able to pay in exploiting springs Tataneyan. The total value of economic benefits can be used as a reference for local communities in the utilization and management of water in the spring Tataneyan.Keywords : Economic Valuation, Water Resources, WTP ( Willingness to pay), Kinilow, Tomohon